2021
DOI: 10.3390/medicina57121382
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented Paravenous Retinochoroidal Atrophy: A Case Report Supported by Multimodal Imaging Studies

Abstract: Background and Objectives: Pigmented paravenous retinochoroidal atrophy (PPRCA) is a rare disease with bilateral retinal pigment epithelium and choroidal atrophy. We present a case of PPRCA using multimodal imaging studies. Case summary: A 61-year-old female was referred to our department for floaters. Funduscopic examination revealed pigment clumps and grayish lesions along the retinal vein and the peripheral area, bilaterally. She did not have nyctalopia or any other visual symptoms including visual loss. Sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
8

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(29 citation statements)
references
References 11 publications
0
3
0
8
Order By: Relevance
“… 12 Optical coherence tomography angiography (OCT-A) has been recently utilized to investigate pathological alterations in vessel density and choriocapillaris porosity in patients with PPCRA. 12 , 13 , 14 , 15 , 16 These reports provide evidence of choriocapillaris hypoperfusion and reduced vessel density in the deep capillary plexus of the retina in this condition. 13 , 16 …”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“… 12 Optical coherence tomography angiography (OCT-A) has been recently utilized to investigate pathological alterations in vessel density and choriocapillaris porosity in patients with PPCRA. 12 , 13 , 14 , 15 , 16 These reports provide evidence of choriocapillaris hypoperfusion and reduced vessel density in the deep capillary plexus of the retina in this condition. 13 , 16 …”
Section: Introductionmentioning
confidence: 66%
“… 29 , 30 In 2021, Jung et al published a case report detailing wide fluorescein angiography (FA), wide indocyanine green angiography (ICGA), optical coherence tomography angiography (OCT-A), and electroretinogram (ERG) findings in order to help clinicians distinguish PPCRA from other pigmentary retinopathies, such as retinitis pigmentosa, hydroxychloroquine retinopathy, or serpiginous choroidopathy. 15 More recent studies using OCT-A in patients with PPCRA have demonstrated alterations in vessel perfusion and density. Lee et al describe the OCT-A imaging characteristics of eyes affected by PPCRA.…”
Section: Discussionmentioning
confidence: 99%
“…L'atrophie rétinochoroïdienne paraveineuse pigmentée (ARPP) est un trouble rare de la rétine et de la choroïde. Bien que l'étiologie soit inconnue à ce jour, on a émis l'hypothèse de pathologies inflammatoires et héréditaires [1][2][3] . L'affection se caractérise par une atrophie de l'épithélium pigmentaire rétinien et une dégénérescence des photorécepteurs, une atrophie de la choriocapillaire et une accumulation de pigments autour des veines rétiniennes rayonnant à partir du nerf optique.…”
Section: Introductionunclassified
“…L'autofluorescence du fond d'oeil est considérée comme la meilleure modalité d'imagerie, car elle permet de capturer l'étendue de l'atrophie rétinochoroïdienne associée aux lésions de l'ARPP. Cette atrophie se manifeste par des lignes de séparation entre les zones actuellement touchées (hyperautofluorescence) et les zones précédemment touchées/ endommagées (hypoautofluorescence) 2,3,13 . Les zones spécifiques d'hypoautofluorescence doivent correspondre aux zones de lésions de la rétine externe mises en évidence par l'angiographie à la fluorescéine et la tomographie par cohérence optique 2 .…”
unclassified
“…Pigmented paravenous retinochoroidal atrophy (PPRCA) is a rare disease of unknown etiology, although dysgenetic, degenerative, hereditary, and inflammatory causes have been suggested. It is usually slowly progressive, and visual acuity remains good unless the macula is involved . Given the personal history of autoimmune disease and a negative genetic test result, a diagnosis of presumed autoimmune PPRCA was suggested.…”
mentioning
confidence: 99%